Down-Regulation of Flagellar, Fimbriae, and Pili Proteins in Carbapenem-Resistant Klebsiella pneumoniae (NDM-4) Clinical Isolates: A Novel Linkage to Drug Resistance - Sharma, Divakar; Garg, Anjali; Kumar, Manish; Rashid, Faraz; Khan, Asad U. (Frontiers in Microbiology, 2019)
Emergence and spread of carbapenem resistant Klebsiella pneumoniae infections worsened the current situation worldwide,which further lead to the visibility of the totally drug resistant strains (bad bugs). Bacterial biofilms makes the bacteria to tolerate the higher dose of antibiotics and other stresses which may lead to the resistance. In the present study we have performed the proteomics of the carbapenem resistant NDM-4 producing K.pneumoniae clinical isolate under the meropenem stress.LC-MS/MS analysis revealed that 69 proteins were down regulated (≤0.42 folds change) under meropenem exposure. Among the identified down regulated proteome (69) we have found a bunch of proteins (13) involved in flagellar, fimbriae, pili formation and their related functions. Further,system biology approaches were employed to reveal their networking pathways.We suggest that these down regulated proteins and their interactive partners cumulatively contributed to the emergence of biofilms like state and survival of bacteria under drug pressure which could explore the novel mechanisms or pathways involved indrug resistance. These down-regulated proteins and their pathways might be used as targets for the development of novel therapeutics against the antimicrobial resistance (AMR) infections.